Transformasi Perilaku Anak Pasca Belajar di TPA Al-Khairiah Langsa Aceh - Hayati, Mir’atil; Mohd. Nasir; Syarifah Hafni (QuranicEdu: Journal of Islamic Education, 2025)
This study aimed to analyze changes in children's behavior after participating in learning at TPA Al-Khairiah Langsa Aceh. The researchers used a qualitative approach with observation, interview, and documentation techniques. The study results showed that learning at TPA Al-Khairiah Langsa contributed significantly to increasing children's awareness of the importance of worship, discipline, and noble morals. The main supporting factors included learning methods based on Islamic values, role models from teachers, and active family involvement in the education process. However, obstacles such as lack of social environmental support and limited learning time at TPA were challenges that need to be overcome. TPA Al-Khairiah Langsa had a strategic role in shaping children's behavior with Islamic character. The resulting recommendation was to increase collaboration between TPA, family, and community to create a conducive environment for the formation of positive behavior in children. It was expected to support the development of children's character holistically in facing the challenges of modern life.